Researching the Intersection of Local and Academic Knowledge on Gender: Academics Working With Community-Based Women’s Organizations - Nancy Peters; Leona M. English; Catherine Irving (Adult Education Research Conference, 2007)
Recognizing the key role women’s organizations contribute to adult learning, this roundtable discussion will explore issues and opportunities that grow out of partnerships between academic researchers and community-based organizations. Participants are invited to share their experiences of researching in such a collaborative environment.